Exclusive rewards in mutualisms: ant proteases and plant protease inhibitors create a lock–key system to protect Acacia food bodies from exploitation. Issue 15 (17th May 2013) - Orona‐Tamayo, Domancar; Wielsch, Natalie; Blanco‐Labra, Alejandro; Svatos, Ales; Farías‐Rodríguez, Rodolfo; Heil, Martin
Abstract: Myrmecophytic Acacia species produce food bodies (FBs) to nourish ants of the Pseudomyrmex ferrugineus group, with which they live in an obligate mutualism. We investigated how the FBs are protected from exploiting nonmutualists. Two‐dimensional gel electrophoresis of the FB proteomes and consecutive protein sequencing indicated the presence of several Kunitz‐type protease inhibitors (PIs). PIs extracted from Acacia FBs were biologically active, as they effectively reduced the trypsin‐like and elastase‐like proteolytic activity in the guts of seed‐feeding beetles ( Prostephanus truncatus and Zabrotes subfasciatus ), which were used as nonadapted herbivores representing potential exploiters. By contrast, the legitimate mutualistic consumers maintained high proteolytic activity dominated by chymotrypsin 1, which was insensitive to the FB PIs. Larvae of an exploiter ant ( Pseudomyrmex gracilis ) taken from Acacia hosts exhibited lower overall proteolytic activity than the mutualists. The proteases of this exploiter exhibited mainly elastase‐like and to a lower degree chymotrypsin 1‐like activity. We conclude that the mutualist ants possess specifically those proteases that are least sensitive to the PIs in their specific food source, whereas the congeneric exploiter ant appears partly, but not completely, adapted to consume Acacia FBs. By contrast, any consumption of the FBs by nonadapted exploiters would effectively inhibit their digestive capacities. We suggest that the term 'exclusive rewards' can be used to describe situations similar to the one that has evolved in myrmecophytic Acacia species, which reward mutualists with FBs but safeguard the reward from exploitation by generalists by making the FBs difficult for the nonadapted consumer to use. Abstract : See also the Perspective by Bronstein